Apoptosis Neuronal pada Penyakit Neurodegeneratif - Sigit Sutanto (Fakultas Kedokteran Universitas Kristen Indonesia, 2007)
Abstrak Selama dekade terakhir, penelitian mengenai mekanisme apoptosis yang kompleks pada kerusakan sel saraf akut maupun kronik telah mengalami banyak kemajuan. Mekanisme apoptosis yang terdiri atas berbagai jalur telah banyak dimengerti, hal itu membuka kemungkinan untuk menginhibisi jalur tersebut untuk membatasi kerusakan yang diakibatkan kematian sel. Selain trauma saraf akut dan iskemia, penyakit neurodegeneratif kronik seperti Alzheimer, Huntington, Parkinson, dan Lou-Gehrig (Amyotrophic lateral sclerosis; ALS) juga menarik perhatian mengingat kesamaan proses yang terjadi yakni apoptosis neuronal. Kata kunci: kematian sel terprogram, neuronal, kaspase, proses neurodegenerasi. Abstract Neuronal Apoptosis in Neurodegenerative Disease during the last decade, the investigation of complicated apoptotic mechanisms in the acute and chronic neuronal cells injury have been improved significantly. The understanding of apoptosis events and its regulation indicate a possible alternate pathway to inhibit the neuronal cells· death. Beside the acute neuronal trauma and ischemia, chronic neurodegenerative diseases such as Alzheimer’s, Huntington’s, Parkinson’s and amyotrophic lateral sclerosis (ALS; Lou Gehrig s disease) are of particular interestdue to the same cause of neuronal apoptosis underlying the diseases. This article will deal with the basic mechanisms of neuronal apoptosis of the above-mentioned disorders. Furthermore, the potential as well as the limitation in clinical applications will be discussed. Finally, this article will also discuss potential implications for the neuronal degenerative diseases future studies. Keywords : programmed cell death, neuronal, caspases, neurodegeneration.